"Caballito blanco, ¡vuelve pa' tu pueblo!": Troubling and reclaiming the historical foundations of Chilean early childhood education. Issue 2 (June 2017) - Castillo, Ximena Galdames
In accordance with the white patriarchal foundations of the early childhood education field of the global north, Chile's early childhood education has a colonial and androcentric origin which has been left unquestioned. Reviews of Chilean early childhood education omit/ignore other socio-political agendas, such as class, gender, and ethnicity that still shape the current landscape. This article reconstructs the foundations of Chilean early childhood education through a reconceptualized mestiza history of the present . This approach challenges the neutrality of Chilean early childhood education and seeks to reclaim it by examining the underpinning regimes of truth that re-colonize children and women moving within and inhabiting the field. Analyses show how two main strands shape(d) early childhood education and care: social (and currently, multiagency) policies, and curriculum and pedagogy. The relationship between these strands has been recursive and contradictory and overlapping over time. However, their mixture creates an illusion of literal transposition as a syncretic effect, which under close examination exposes its fault lines.